The investment behaviour of dairy farms in transition economies. Issue 1 (2nd January 2021) - Fertő, Imre; Bojnec, Štefan; Fogarasi, József; Viira, Ants Hannes
ABSTRACT: This article investigates dairy farm investment behaviour and the presence of soft budget constraints in the dairy farms of Baltic and Central European transition countries – Estonia, Hungary and Slovenia – using individual dairy farm accountancy panel data for the years 2007–2015. The empirical results confirm that gross dairy farm investment is positively associated with gross dairy farm investment for the previous year for financially unconstrained dairy farms, and negatively for financially constrained dairy farms. It is also positively associated with public investment subsidies, and, except for Slovenia, with growth in real sales for financially unconstrained dairy farms. Mixed results are found for gross dairy farm investment squared and cash flow variables. A particularly significant negative cash flow regression coefficient implies significant soft budget constraints for financially unconstrained Estonian and Slovenian dairy farms, while insignificant cash flow regression coefficients imply weak soft budget constraints for financially unconstrained Hungarian dairy farms.